2009
DOI: 10.1007/s00300-009-0749-4
|View full text |Cite
|
Sign up to set email alerts
|

Vagrant Antarctic fur seals at Gough Island in 2009

Abstract: The Antarctic fur seal Arctocephalus gazella at Gough Island (40°20ЈS, 09°54ЈW) in the South Atlantic Ocean, Wrst seen in October/November 2005, was recorded again in September-October 2009. Up to three diVerent individual Antarctic fur seals were sighted on a single day, on a particular beach. A total of seven diVerent individuals were recorded over a 3-week period, well before the onset of the breeding (pupping) season of the resident population of Subantarctic fur seals A. tropicalis. Positively identiWed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…Antarctic fur seals Arctocephalus gazella mainly breed at localities south of the Antarctic Polar Front, but have successfully colonised some sub-Antarctic islands north of this Front (Condy 1978;Bester 1984), where they are largely replaced by the Subantarctic fur seal A. tropicalis. Vagrant Antarctic fur seals occasionally occur farther north (Acevedo et al 2011), reaching Gough Island (40°S, 10°W) in the central South Atlantic Ocean (Wilson et al 2005;Bester and Reisinger 2010), and we report a further range extension in this region.…”
supporting
confidence: 58%
See 1 more Smart Citation
“…Antarctic fur seals Arctocephalus gazella mainly breed at localities south of the Antarctic Polar Front, but have successfully colonised some sub-Antarctic islands north of this Front (Condy 1978;Bester 1984), where they are largely replaced by the Subantarctic fur seal A. tropicalis. Vagrant Antarctic fur seals occasionally occur farther north (Acevedo et al 2011), reaching Gough Island (40°S, 10°W) in the central South Atlantic Ocean (Wilson et al 2005;Bester and Reisinger 2010), and we report a further range extension in this region.…”
supporting
confidence: 58%
“…2b). Despite the 5day lapse between the sightings at TdC and 380 km distant Gough Island (GI), where it was seen in the same area as previous sightings (Wilson et al 2006;Bester and Reisinger 2010), it is impossible to say whether it is the same animal.…”
mentioning
confidence: 97%
“…The subantarctic fur seal Arctocephalus tropicalis suffered severe population reductions and local extinctions due to commercial exploitation. After sealing, pronounced population expansions and recolonization of historical sites, and probable colonization of new breeding sites occurred (Wynen et al 2001), and the species was found outside its range in South America, Angola, New Zealand, Australia, South Africa and on several islands (for a review, see Bester & Reisinger 2010). Ferreira et al (2008) analysed mtDNA control region sequences from vagrant subantarctic fur seals found on the Brazilian coast and from animals from the main breeding colonies.…”
Section: Order Carnivora Familiy Mustelidaementioning
confidence: 99%
“…After sealing, pronounced population expansions and recolonization of historical sites, and probable colonization of new breeding sites occurred (Wynen et al. 2001), and the species was found outside its range in South America, Angola, New Zealand, Australia, South Africa and on several islands (for a review, see Bester & Reisinger 2010). Ferreira et al.…”
mentioning
confidence: 99%
“…For example, some AFS populations are declining in part of their distribution range (Forcada and Hoffman ), but not elsewhere. Fur seals are able to travel extensive distances ( e.g ., Bester and Reisinger , Bester et al . ) and settle at new rookeries (Wynen et al .…”
Section: Resultsmentioning
confidence: 99%